Inflammation and Coagulation are Two Interconnected Pathophysiological Pathways in Atrial Fibrillation Pathogenesis - Hazarapetyan L; Zelveian PH; Grigoryan S (Journal of Inflammation Research, 2023)
Lusine Hazarapetyan,1,2 Parounak H Zelveian,2 Svetlana Grigoryan1,2 1Department of Cardiology, Yerevan State Medical University Named After M. Heratsi, Yerevan, Armenia; 2Scientific Research Institute of Cardiology Named After L Hovhannisyan, Yerevan, ArmeniaCorrespondence: Svetlana Grigoryan, Department of Cardiology, Yerevan State Medical University, 5 P. Sevak Street, Yerevan, 0044, Armenia, Tel +374-91-415 − 123, Email s.grigoryan@interdiagnostika.comIntroduction: Atrial fibrillation (AF) is associated with elevated levels of clotting factors such as tissue factor (TF) and factor XII (FXII). Various inflammation markers, such as interleukin-6 (IL-6), tumor necrosis factor-α (TNF- α), and high-sensitive C-reactive protein (hs-CRP), have also been associated with AF. This study explores the relationship between inflammation markers and coagulation activity, including their impact on heart structural changes in these patients.Methods: We observed 283 patients with nonvalvular AF who underwent a complete examination at admission, but only 183 patients have successful cardioversion. As a control group, similar patients without AF were examined. The markers of the coagulation and inflammation were studied by ELISA on the analyzer “Stat Fax 303 Plus”. Studies were conducted using l statistical package SPSS 13.0.Results: It was revealed that patients with AF had significantly higher levels of hs-CRP, IL-6, and TNF-α and had elevated levels of TF and FXII compared with control group. The moderate correlations were observed between IL-6 and left atrial diameter (LAD), IL-6 and LA stiffness, hs-CRP and left atrial volume (LAV), TF and LAV.Conclusion: We have demonstrated that patients with AF have the relationship between elevated levels of inflammatory markers and coagulation activity, which contributes to structural atrial remodeling.Keywords: atrial fibrillation, hs-C reactive protein, interleukin-6, tissue factor, factor XII